Treatment Effect of Long-Term Antipsychotics on Default-Mode Network Dysfunction in Drug-Naïve Patients With First-Episode Schizophrenia: A Longitudinal Study - Deng, Mengjie; Liu, Zhening; Shen, Yanyu; Cao, Hengyi; Zhang, Manqi; Xi, Chang; Zhang, Wen; Tan, Wenjian; Zhang, Jinqiang; Chen, Eric; Lee, Edwin; Pu, Weidan (Frontiers in Pharmacology, 2022)
Background: The maintenance of antipsychotic treatment is an efficient way to prevent the relapse of schizophrenia (SCZ). Previous studies have identified beneficial effects of antipsychotics on brain structural and functional abnormalities during mostly acute phase in SCZ, but seldom is known about the effects of long-term antipsychotics on the brain. The present study focused on the long-term antipsychotic effect on the default mode network (DMN) dysfunction in SCZ. Methods: Longitudinal study of functional connectivity (FC) of 11 DMN subdivisions was conducted in 86 drug-naive first-episode patients with SCZ at baseline and after long-term atypical antipsychotic treatment (more than 6 months) based on resting-state functional magnetic resonance image. In total, 52 patients completed the follow-up clinical and neuroimaging investigations. Results: At baseline, relative to healthy controls, altered connectivity within the DMN and between the DMN and the external attention system (EAS) were observed in patients. After treatment, along with significant relief of symptoms, most FC alterations between the DMN and the EAS at baseline were improved after treatment, although the rehabilitation of FC within the DMN was only observed at the link between the posterior cingulate cortex and precuneus. Greater reductions in negative and positive symptoms were both related to the changes of DMN-EAS FC in patients. Conclusions: Our findings provide evidence that maintenance antipsychotics on SCZ is beneficial for the improvement of DMN-EAS competitive imbalance, which may partly contribute to the efficient relapse prevention of this severe mental disorder.